Kehidupan Mangaka Dalam Manga Bakuman Karya Tsugumi Ohba Dan Takeshi Obata - Winda Trisna Dewi, Ni Putu; Ari Sulatri, Ni Luh Putu; Yuliani Giri, Ni Luh Kade (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
The research describe the life of mangaka and people opinion of the occupation of mangaka in the manga Bakuman by Tsugumi Oh b a and Takeshi Obata . The data analyzed using descriptif analysis and dialetic method . This research used the sociology of literature by Watt (in Damono, 1979:3-5) and semiotic theory by Danesi (2010:7) . The result is the life of mangaka in the manga Bakuman is going through several processes. These processes are learning the technique of making manga, contacting the editorial, joining competition, geting an editor, making a 'name', publishing a manga in magazine and serilize it, then turn it into anime. The working situation of a mangaka covering the mangaka' s workplace, the mangaka's working hours, the mangaka working with the assistants. The economic condition of mangaka covering the mangaka earn money from their salary and royalty. In the manga Bakuman also found the opinion of people of mangaka. The opinion is that from mangaka itself in which mangaka need a high skill of drawing and writing a story and also mangaka is a desired accupation by the youngster of Japan. Opinion from the co-worker, in which mangaka has a heavy workload, but it give a good income. The opinion from the mangaka's family is that the occupation of mangaka decrease the time that the mangaka spend with family , h o wever it helps the economy of the family.